(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Background: Type ІІ diabetes mellitus is a common disease across the world. It is responsible for the development of various macro- and micro-vascular complications in many organs of the body. The association between lung function and late stages diabetic nephropathy had been illustrated in many previous studies. This study aimed to explore if there was association between early stages diabetic nephropathy and changes in pulmonary function. Methods: This case-control study was performed on patients who had early stages diabetic nephropathy (micro-albuminuria i.e. urinary albumin=30-300 mg/day), it included 78 patients who had diabetes with micro-albuminuria, 72 patients who had only diabetes without micro-albuminuria and 80 healthy subjects as a control group, full history was taken and physical examination was performed on all the patients, in addition to the following needed investigations: Urine albumin, random blood sugar, blood urea, serum creatinine, pulmonary function tests and pulse oximeter. Results: This study revealed that there was no significant difference in ages, gender and body mass index (BMI) among groups. Duration of diabetes ranged from 3 to 8 years, all patients had type 2 diabetes mellitus. The levels of random blood sugar, blood urea, and serum creatinine were normal in all subjects. The spirometric changes [forced vital capacity (FVC % predicted) and forced expiratory volume in 1 second (FEV1 % predicted)] were significantly lower in diabetic patients with micro-albuminuria than those who had no micro-albuminuria (P<0.05). In addition, there was no significant difference in the spirometric changes between males and females in both groups. This study also revealed that in group of patients with positive micro-albuminuria (MAU), the percentage of those with positive spirometric changes was more in group of patients with increased body mass index than those with normal body mass index (P<0.05). Also this study shows that the patients with increased weight and positive micro-albuminuria had positive spirometric changes when compared to those without micro-albuminuria (P<0.05). The mean levels of oxygen saturation (SpO2) was normal in both diabetic groups. Conclusions: This study showed that there was a disturbance of lung function in patients with early stages diabetic nephropathy (micro-albuminuria). The combination of micro-albuminuria and increased body weight had more effects on lung function than others who had normal body weight.